"It is not just about the alcohol": service users' views about individualised and standardised clinical assessment in a therapeutic community for alcohol dependence. Issue 1 (December 2016) - Alves, Paula; Sales, Célia; Ashworth, Mark
Abstract Background The involvement of service users in health care provision in general, and specifically in substance use disorder treatment, is of growing importance. This paper explores the views of patients in a therapeutic community for alcohol dependence about clinical assessment, including general aspects about the evaluation process, and the specific characteristics of four measures: two individualised and two standardised. Methods A focus group was conducted and data were analysed using a framework synthesis approach. Results Service users welcomed the experience of clinical assessment, particularly when conducted by therapists. The duration of the evaluation process was seen as satisfactory and most of its contents were regarded as relevant for their population. Regarding the evaluation measures, patients diverged in their preferences for delivery formats (self-report vs. interview). Service users enjoyed the freedom given by individualised measures to discuss topics of their own choosing. However, they felt that part of the standardised questions were difficult to answer, inadequate (e.g. quantification of health status in 0–20 points) and sensitive (e.g. suicide-related issues), particularly for pre-treatment assessments. Conclusions Patients perceived clinical assessment as helpful for their therapeutic journey, including the opportunity to reflect about their problems, either related or unrelated to alcohol use. Our study suggests that patients prefer to have evaluation protocols administered by therapists, and that measures should ideally be flexible in their formats to accommodate for patient preferences and needs during the evaluation.